Biophysical studies of two viruses : Cucumber mosaic virus and Nudaurelia non-inclusion virus - Hendry, D. A.(Donald Arthur) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc) -- University of Stellenbosch, 1969.